2020
DOI: 10.1111/trf.15638
|View full text |Cite
|
Sign up to set email alerts
|

Use of a cloud‐based search engine of a centralized donor database to identify historical antigen‐negative units in hospital inventories

Abstract: BACKGROUND: The provision of units with antigennegative attributes is required for alloimmunized transfusion recipients and to avoid alloimmunization among patients on chronic transfusion support. Recent evidence confirms that the demand for antigen-typed units is increasing. STUDY DESIGN AND METHODS:A cloud-based search engine was designed by the blood center to find antigen-negative units. The service provided access to historical antigen information for units in hospital inventories. The hospital transfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Some studies have reported new methods for transfusion services to easily identify antigen-negative units from repeat donors. 25 Others have shown that requests for antigen-negative units are placing an increasing burden on blood centers. 26,27 While prophylactic matching for patients receiving daratumumab appears unnecessary in the current climate, technological advances could make the practice more favorable in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported new methods for transfusion services to easily identify antigen-negative units from repeat donors. 25 Others have shown that requests for antigen-negative units are placing an increasing burden on blood centers. 26,27 While prophylactic matching for patients receiving daratumumab appears unnecessary in the current climate, technological advances could make the practice more favorable in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of prophylactic matching, of course, depends on resources and technology. Some studies have reported new methods for transfusion services to easily identify antigen‐negative units from repeat donors 25 . Others have shown that requests for antigen‐negative units are placing an increasing burden on blood centers 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Versiti Blood Centers and Blood Centers of America (BCA) partnered to create such a service-a readily accessible, cloud-based, uncommon unit "exchange" to allow any blood center to request and/or provide information regarding the availability of typed units in their inventory (Figure 4A). 11,12 In order to create this service, several key design questions had to be resolved:…”
Section: Case Study #2: Locating Antigennegative Units For Patientsmentioning
confidence: 99%
“…A blood center non‐proprietary cloud‐based search engine, termed Antigen Query, was developed that allows hospital transfusion services served by the blood center to scan their inventory for historical antigen‐negative units. This search engine serves as a successful screening tool to quickly identify antigen‐negative units using historical data . The transfusion service staff can then confirm the antigen‐negative status using antisera only on those units identified.…”
Section: Descriptionmentioning
confidence: 99%